2008
DOI: 10.1183/09031936.00103507
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation ofMoraxella catarrhalis-induced interleukin-8 response by protein kinase C isoforms

Abstract: Moraxella catarrhalis is a major cause of infectious exacerbations of chronic obstructive lung disease. In pulmonary epithelial cells, M. catarrhalis induces release of the proinflammatory cytokine interleukin (IL)-8, which plays a pivotal role in orchestrating airway inflammation.The present study demonstrated that protein kinase (PK)C was activated by Moraxella infection and positively regulated M. catarrhalis-triggered nuclear factor (NF)-kB activation and subsequent IL-8 release. Activation of the PKC/NF-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Diverse microbial pathogens stimulate airway epithelial cells, leading to activation of the transcriptional activator NF-B and production of proinflammatory cytokines, such as IL-6 and IL-8 (5,15,20,28,30). In this study, we observed that CS inhibited IL-8 production brought about by NT H. influenzae and S. aureus in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 55%
“…Diverse microbial pathogens stimulate airway epithelial cells, leading to activation of the transcriptional activator NF-B and production of proinflammatory cytokines, such as IL-6 and IL-8 (5,15,20,28,30). In this study, we observed that CS inhibited IL-8 production brought about by NT H. influenzae and S. aureus in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 55%
“…In a previous study, PKCa has been shown to be important for COX-2 expression and subsequent PGE 2 release in L. pneumophila-infected alveolar epithelial cells [4]. Also, we demonstrated that Moraxella catarrhalis infection activates PKCa, e, and h which differentially regulate interleukin-8 gene transcription in human pulmonary epithelial cells [14]. Since the activation pattern of PKCs as well as their impact on inflammatory immune response depends on the pathogen implicated, the above described mechanism might be specific for a L. pneumophila.…”
Section: Discussionmentioning
confidence: 97%
“…To clear L. pneumophila from the lung, a functionally intact innate immune system, particularly macrophages and polymorphonuclear leukocytes (PMNs), must be present [3,8]. Epithelial cells have been shown to liberate mediators such as granulocytemacrophage colony-stimulating factor (GM-CSF), interleukin-8, interferon (IFN)-b, and prostaglandin (PG)E 2 upon infection [4,5,[11][12][13][14]. GM-CSF is a 23-kDa haematopoietic growth factor that is able to stimulate in vitro survival, proliferation, differentiation and function of myeloid cells and their precursors, particularly PMNs, eosinophils, granulocytes, and monocytes/macrophages [15,16].…”
mentioning
confidence: 99%
“…The chromatin immunoprecipitation was performed as described previously (45). A549 cells were stimulated 1 h prior to fixation.…”
Section: Materials and Antibodiesmentioning
confidence: 99%